Total blood protein as an indicator of colostral sufficiency and morbidity in dairy calves - D.G. Schmidt; D.P. Gnad; J.M. Sargeant; John E. Shirley (Kansas Agricultural Experiment Station Research Reports, 2000)
Total blood protein measured in calves between 1 and 7 days of age is a good indicator of the sufficiency of colostral intake and level of immunity passed to the calf. This measurement can be used to improve calf management strategies and thereby calf performance. Total blood protein concentrations are associated with immunoglobulin absorption in the neonatal calf, which can impact calf morbidity and mortality. Blood protein>5.5 g/dl indicates sufficient immunoglobulin absorption, and blood protein <5.0 g/dl indicates insufficient absorption. Insufficient immunoglobulin absorption increases the risk of calf morbidity and mortality. The dry cow health program, proper collection, and management of colostrum help ensure that quality colostrum is available for the newborn calf. Proper colostrum administration and low-stress calf management also ensure maximal immunoglobulin absorption. Timing of colostral intake affects total blood protein concentrations. The calf's ability to absorb immunoglobulins is reduced significantly 12 hr after birth. Therefore, it is critical to administer colostrum during the first few hours of life. Total blood protein can be used to determine if the calf has absorbed sufficient immunoglobulins from the colostrum.; Dairy Day, 2000, Kansas State University, Manhattan, KS, 2000;
Keywords: Dairy Day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-166-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 861; Dairy; Blood protein; Colostrum; Calves; Morbidity